Electric vehicle sharing based “energy sponge” service interfacing transportation and power systems - Qianwen Li; Dongfang Zhao; Xiaopeng Li; Xin Wang (Cleaner Logistics and Supply Chain)
Electrical vehicles (EVs) by the nature of the technology assume a dual role of supplying transportation mobility and storing electric power. Thus, the operations of EV impact both transportation and power grid systems. This study proposes the concept of an “energy sponge” service by de- signing an EV sharing system serving both a transportation system and a power market. The proposed model investigates operations of a fleet of EVs that may opt to serve the transportation system when the transportation demand is high or return electricity to the grid when the power price shoots high. A Markov decision model is proposed to determine the optimal policy on time allocation of the EV fleet over the two systems. A dynamic programming algorithm is developed to solve the model efficiently. Real-world data on the configurations of these two markets are used to build numerical examples. Sensitivity analyses are constructed to draw insights into the benefits and operational patterns of the service. Overall, this model provides methods and insights for EV fleet managers to decide optimal policies for allocating the EV fleet between transportation and power markets. Besides shared mobility systems, this model also has great potential in other logistics and supply chain systems where EVs are used to deliver goods or services.